2002
DOI: 10.1007/3-540-45748-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Gnutella Network: Macroscopic Properties of Large-Scale Peer-to-Peer Systems

Abstract: Despite recent excitement generated by the peer-to-peer (P2P) paradigm and the surprisingly rapid deployment of some P2P applications, there are few quantitative evaluations of P2P systems behavior. The open architecture, achieved scale, and self-organizing structure of the Gnutella network make it an interesting P2P architecture to study. Like most other P2P applications, Gnutella builds, at the application level, a virtual network with its own routing mechanisms. The topology of this virtual network and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
451
2
8

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 465 publications
(467 citation statements)
references
References 15 publications
6
451
2
8
Order By: Relevance
“…3. Utilization of the underlying network: a global property that is of interest to network service providers, measured by the metrics like the physical distance (latency) to the search results, and the mean stress, one of the most common definitions of the traffic load in overlay network [21].…”
Section: Evaluation Methodsologymentioning
confidence: 99%
“…3. Utilization of the underlying network: a global property that is of interest to network service providers, measured by the metrics like the physical distance (latency) to the search results, and the mean stress, one of the most common definitions of the traffic load in overlay network [21].…”
Section: Evaluation Methodsologymentioning
confidence: 99%
“…The proposals presented in [23,24,28] studied traces of P2P applications such as Gnutella and Napster. These works focused on characterizing the overall P2P system, e.g., request patterns, traffic volume, traffic categorization and properties of shared online content as well as P2P structure and dynamics, e.g., connectivity and peer behaviors.…”
Section: Related Workmentioning
confidence: 99%
“…These works focused on characterizing the overall P2P system, e.g., request patterns, traffic volume, traffic categorization and properties of shared online content as well as P2P structure and dynamics, e.g., connectivity and peer behaviors. In particular the papers [23,24] presents a quantitative evaluations of P2P system behaviors and it is based on a "crawler" to extract topology of Gnutella application level network and brings to conclude that, although Gnutella is not a pure power-law network, its configuration has benefits and drawbacks of a power-law structure, e.g., resilience to random peer failures.…”
Section: Related Workmentioning
confidence: 99%
“…However, unstructured P2P networks pose significant challenges. For example Gnutella is known to consume high bandwidth [18]. Other studies [19] have shown that P2P systems exhibit high churn (changes in system membership); peers frequently leave/join the network and most peers are connected to the overlay for a short period of time.…”
Section: Introductionmentioning
confidence: 99%